Bidding Strategies in Agent-Based Continuous Double Auctions - Ma, Huiye. (Whitestein Series in Software Agent Technologies and Autonomic Computing, 2008)
Online auctions are a platform to trade goods on the Internet. In this context, negotiation capabilities for software agents in continuous double auctions (CDAs) are a central concern. Agents need to be able to prepare bids for and evaluate offers on behalf of the users they represent with the aim of obtaining the maximum benefit for their users. For the agents, their bids are decided according to some bidding strategy. However, in CDAs, it is a complex decision problem because of the inherent uncertainty and dynamics of the auction market. In this book, we present a new bidding strategy for agents to adopt in CDAs and propose tools to enhance the performance of existing bidding strategies in CDAs. The superior performance of the new bidding strategy as well as the tools presented in this book are illustrated through extensive experiments.